The role of prosumers in the evolution of a software ecosystem: Case Steam - Tapani N. Joelsson; Sami Hyrynsalmi; Sabine Molenaar (Germany, 2022)
This paper examines two questions: what is the role of active users or prosumers —i.e. users who consume as well as produce—in the transformation of a software ecosystem during its lifespan, and how does a digital marketplace transform into an ecosystem. This approach departs from the extant literature where consumers of an ecosystem are often treated only as passive participants. In this study, the role of prosumers is studied by portraying the transformation of Steam , by Valve Corporation, and discussed how it fits in the current field of software ecosystem research as well as what has been the impact of prosumers in its transformation process. The results from this case highlight the importance of users’ active role in the evolution. Besides the discussion on the status of prosumers and the ecosystem evolution, the inner structure of this ecosystem is highlighted in the findings.
Proceedings of the International Workshop on Software-intensive Business: Start-ups, Ecosystems and Platforms (SiBW 2018)